Vidékfejlesztési támogatások lehetőségei a régiós faipari mikro-, kis- és középvállalkozásoknál - Bartos György (2017)
In my degree thesis I describe the market situation of the local micro-, small- and medium- sized companies through the summery of the history of the timber industry. I point it out, through analyzing its causal relations, what the reason for the disappearance of the big companies employing over 250 people was, and why micro- and small companies became the most popular business form in the timber industry. In my degree thesis I present the opportunities and also the making use of regional development tenders supported by the European Union at 13 regional timber businesses, in which I demonstrate the present tender cycle and the system of the tender through the result of my primary research. We can state, based on the personal interviews and the surveys, that the opportunities provided by the regional development tenders are not at all, or only to a smaller degree utilized. It became obvious, that it is caused by the complexity of the tender system, and at the same time, by the uncertainty of the market position of the small businesses. The respondents confirmed, that on the one hand, the period of the tender judgement was way too long, on the other hand, their uncertainty was influenced by the recession just as much as by the seasonal character of certain timber sections. Yet, we can state, that the financial support, provided by the European Union through tenders and many other ways, can influence the economic growth of the timber sector in the long run. But how could advantage be taken of these sources and which tenders are there to be relevant for the timber companies? The purpose of my degree thesis, beside answering for the above mentioned questions is to work out a strategy for the timber companies, which makes them interested- either directly or inderectly- in making use of sources of tenders, which could empower them to increase their income. My degree thesis is special from that aspect, that noone has ever studied the opportunities of development and use of European Union regional development tenders in the timber industry before.